Youth and the democratic deficit. - Wesley, Jared J. (Inroads)
The article reviews the book "The Internet Generation: Engaged Citizens or Political Dropouts," by Henry Milner and "Citizens Adrift: The Democratic Disengagement of Young Canadians," by Paul Howe.